Penggunaan Media Bangun Datar dari Kertas Origami terhadap Minat Belajar Peserta Didik pada Materi Mengenal Macam-Macam Bangun Datar di Kelas II SD Katolik Santa Maria Kalabahi - Marta Etding; Melki I. Puling Tang; Yermia S. Wabang; Imanuel Puling (STIKes Ibnu Sina Ajibarang, 2025)
This research aims to illustrate the implementation of flat-shaped learning media from origami paper in mathematics learning for grade 2 at St. Maria Kalabahi Catholic Elementary School. This research was conducted to increase students’ learning interest due to the lack of activity during the learning process. Class teachers usually only use PPT and books for learning in the classroom, making the learning process monotonous. The research method used is descriptive quantitative. Data collection techniques use observation and documentation. Data analysis techniques use descriptive quantitative. Based on the results of the research and data analysis, it is concluded that students have enthusiasm and interest in learning, so they can more easily understand the learning material delivered by the teacher. Students are interested in daring to find and discover various flat shapes made from origami paper and stick them to the name column of the flat shape correctly.